Review of / Reseña de: Bohoslavsky, Juan Pablo y Mariana Rulli. Deuda feminista: ¿Utopía u oxímoron? La Plata: EDULP, 2023. 537 pp. ISBN: 978-987-8475-99-8 - Noelia Verónica Méndez Santolaria (Feminismo/s)
Review of / Reseña de: Bohoslavsky, Juan Pablo y Mariana Rulli. Deuda feminista: ¿Utopía u oxímoron? La Plata: EDULP, 2023. 537 pp. ISBN: 978-987-8475-99-8.